IMPROVING EFFORTS OF CRITICAL THINKING OF STATISTICS MATERIAL USING PROBLEM BASED LEARNING MODEL IN FIFTH GRADE MELUNG ELEMENTARY SCHOOL - Laelly Wahyuningsih; Wahyudi Wahyudi (Universitas Negeri Medan, 2019)
Abstract :The purpose of this study was to describe the application of the Problem Based Learning model to improving student’s critical thinking skills on Mathematics subjects in the fifth grade statistics material at Melung Elementary School. Problem Based Learning is used to stimulate problem-oriented critical thinking. Through the application of Problem Based Learning, students are expected to be able to find solutions to problems discussed in the learning process. The method used is Classroom Action Research (CAR). There were 66.6% of the students in the